The present prospects of social art history - Slifkin, Robert; Grudin, Anthony E. (New York Bloomsbury Visual Arts, 2021)
The Present Prospects of Social Art History represents a major reconsideration of how art historians analyze works of art and the role that historical factors, both those at the moment when the work was created and when the historian addresses the objects at hand, play in informing their interpretations. Featuring the work of some of the discipline's leading scholars, the volume contains a collection of essays that consider the advantages, limitations, and specific challenges of seeing works of art primarily through a historical perspective. The assembled texts, along with an introduction by the co-editors, demonstrate an array of possible methodological approaches that acknowledge the crucial role of history in the creation, reception, and exhibition of works of art.
Keywords: Art -- Historiography -- Methodology; Art and history